Characterizing Thermal Augmentation of Convection-Enhanced Drug Delivery with the Fiberoptic Microneedle Device. (September 2015) - Hood, R. Lyle; Andriani, Rudy T.; Ecker, Tobias E.; Robertson, John L.; Rylander, Christopher G.
ABSTRACT: Convection-enhanced delivery (CED) is a promising technique leveraging pressure-driven flow to increase penetration of infused drugs into interstitial spaces. We have developed a fiberoptic microneedle device for inducing local sub-lethal hyperthermia to further improve CED drug distribution volumes, and this study seeks to quantitatively characterize this approach in agarose tissue phantoms. Infusions of dye were conducted in 0.6% (w/w) agarose tissue phantoms with isothermal conditions at 15 °C, 20 °C, 25 °C, and 30 °C. Infusion metrics were quantified using a custom shadowgraphy setup and image-processing algorithm. These data were used to build an empirical predictive temporal model of distribution volume as a function of phantom temperature. A second set of proof-of-concept experiments was conducted to evaluate a novel fiberoptic device capable of generating local photothermal heating during fluid infusion. The isothermal infusions showed a positive correlation between temperature and distribution volume, with the volume at 30 °C showing a 7-fold increase at 100 min over the 15 °C isothermal case. Infusions during photothermal heating (1064 nm at 500 mW) showed a similar effect with a 3.5-fold increase at 4 h over the control (0 mW). These results and analyses serve to provide insight into and characterization of heat-mediated enhancement of volumetric dispersal.